EFFECTS OF INACCURATE COST ESTIMATE ON CONSTRUCTION PROJECT STAKEHOLDERS - Abiodun AWOSINA; Ruben NDIHOKUBWAYO; Julius FAPOHUNDA (Journal of Construction Project Management and Innovation)
The aim of this paper is to assess the effects of inaccurate cost estimates on construction project stakeholders in order to establish mitigation measures. The paper reviewed literature relating to cost estimation and the empirical data was obtained through a structured questionnaire. Furthermore, the study involved convenient purposive sampling of construction professionals working in quantity surveying practices and construction firms within and around Cape Town. A quantitative approach was used to conduct the study and data were reported using central tendency descriptive statistics. The findings revealed inaccurate cost estimates resulting in loss of reputation and credibility of project stakeholders, risk exposure, and financial loss as the effects of inaccurate cost on construction projects. In view of the confidential nature of some project costs in the private construction sector, the research experienced limitations in gathering statistics on the actual extent of projects that were underestimated or overestimated for comparative studies on private sector projects. The study draws the attention of construction project stakeholders to the negative effects and consequences of inaccurate cost estimation in order to proffer a mitigating mechanism.